2001
DOI: 10.2105/ajph.91.5.791
|View full text |Cite
|
Sign up to set email alerts
|

Laws prohibiting over-the-counter syringe sales to injection drug users: relations to population density, HIV prevalence, and HIV incidence

Abstract: OBJECTIVES: This study sought to assess relations of laws prohibiting over-the-counter syringe sales (anti-OTC laws) to population prevalence of injection drug users and HIV prevalence or incidence among 96 US metropolitan areas. METHODS: A cross-sectional analysis was used. RESULTS: Metropolitan areas with anti-OTC laws had a higher mean HIV prevalence (13.8% vs 6.7%) than other metropolitan areas (pseudo-P < .001). In 83 metropolitan areas with HIV prevalence of less than 20%, anti-OTC laws were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…These findings could result from greater access to pharmacies that sell non-prescription syringes among PWID in San Francisco, which is consistent with other studies reporting associations between pharmacy use and lower rates of HIV and HCV infection, as well as lower rates of syringe sharing. 4,1416 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings could result from greater access to pharmacies that sell non-prescription syringes among PWID in San Francisco, which is consistent with other studies reporting associations between pharmacy use and lower rates of HIV and HCV infection, as well as lower rates of syringe sharing. 4,1416 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, pharmacies can be a viable source of sterile syringes for PWID due to the increased availability compared to syringe exchange programs; hence decreasing the HIV prevalence of those PWID who purchase syringes from a pharmacy. 4 …”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the predictors of PWID population prevalence (per 10,000 adult population), of HIV prevalence among PWID, and of HIV incidence among PWID. In one analysis, we showed that metropolitan areas in states with laws against over the counter purchase of syringes had higher HIV prevalence rates and incidence rates than those in states where syringes could be purchased (Friedman, Perlis, & Des Jarlais, 2001). In further analyses, we found that income inequality in a metropolitan area (as well as laws against syringe purchase) was positively associated with the population prevalence of PWID and with HIV prevalence rates among PWID (Friedman, Perlis, Lynch, & Des Jarlais, 2001).…”
Section: Findings From Five Analysesmentioning
confidence: 99%
“…14-25 Subsequently, pharmacy syringe sales have been associated with reduced injection mediated-risks 14,26-28 and reduced rates of HIV infection among PWID. 29-31 Non-prescription syringe sales offer the potential for enhancing syringe availability due to the broad distribution of pharmacies throughout most regions of the U.S. and up to 24 hours of operation, 27,32 but syringe sales rates can vary substantially, depending on local legislation and local pharmacy practice. 33 In many states, PWID recognize pharmacies as stable, safe and affordable sources of sterile syringes, 19,34,35 and other services, depending on the training level of the pharmacists.…”
Section: Introductionmentioning
confidence: 99%